The Impact of Perceived Psychological Contract Breach, Abusive Supervision, and Silence on Employee Well-being - Morsch, Jan; van Dijk, Dana; Kodden, Bas (Journal of Applied Business and Economics, 2020)
The aim of this study was to examine the relationship between psychological contract breach as it is perceived by employees, the comprehensiveness of silence and the moderating effect that abusive supervision has on the relationship between psychological contract breach, silence, and indirectly on employee well-being. This study revealed support for the negative relationship between psychological contract breach and employee well-being. Quiescent silence was found to mediate the negative relationship between psychological contract breach and employee well-being. Abusive supervision was found to be a strengthening moderator in the negative relation between psychological contract breach and quiescent silence.